Racial discrimination and the health and wellbeing of Aboriginal and Torres Strait Islander children: Does the timing of first exposure matter? - Cave, Leah; Shepherd, Carrington C J; Cooper, Matthew N; Zubrick, Stephen R (My University, 2019)
Racial discrimination has been observed to negatively impact on the health of Aboriginal and Torres Strait Islander children, although evidence surrounding periods of greater vulnerability to the stressor of racism have not yet been explored in this population. We compared first exposure to interpersonal racism at either ages 4-5 years or 7 years with no exposure to examine the influence of sensitive periods of racism exposure on mental health and physiological outcomes during middle childhood (7-12 years). The study cohort comprised 1,759 Aboriginal and Torres Strait Islander children aged 4-12 years from waves 2-8 (2009-2015) of the Footprints in Time: 1The Longitudinal Study of Indigenous Children (LSIC) dataset. Multilevel logistic regression was used in all analysis. We observed a larger effect (OR: 2.8; 95% CI: 1.4-5.4) for negative mental health with first exposure at 4-5 years compared to 7 years (OR: 2.1; 95% CI: 1.2-3.6), referenced to children with no exposure. Effect sizes were similar in both exposure groups for the significantly increased risk of sleep difficulties, while a stronger adverse effect on behavioural issues was found at 7 years (OR: 2.2; 95% CI: 1.3-4.0) relative to 4-5 years (OR: 1.7; 95% CI: 0.8-3.7). No significant associations were found with general health, obesity or being underweight. This study generates new evidence surrounding sensitive periods of exposure to racism in Aboriginal and Torres Strait Islander children. A pattern of consistently greater adverse effects on mental and physiological health was not observed with first exposure at 4-5 compared to 7 years, although initial evidence indicates that first exposure to racism at these ages increases the likelihood of negative mental health relative to children without racism exposure. Longitudinal data extending from earlier to later developmental periods will allow further investigations into the presence of sensitive periods of exposure to racism in these children.
SSM - Population Health
Keywords: Childhood and child development; Health and wellbeing